A Translation Analysis Of Taboo Word In The Spongebob Movie “Sponge Out Of Water” - Chani Alvionita; dian mukhlisa; chandri febri santi (English Literature Department, Adab and Humanities Faculty, 2021)
The objective of this research is to describe the types, meanings and strategies of the words taboo in the SpongeBob Movie: Sponge Out of Water and the objects in this research are English dialogue and Indonesian subtitles. This research employs descriptive qualitative research. The object of this research is The SpongeBob Movie: Sponge Out of Water. The data of this research are all utterances spoken by nine of characters “SpongeBob, Patrick, Plankton, Mr. Krab, Seagull, Karen, Burger Beard, Sandy and Squidward”. The Spongebob Movie: Sponge Out of Water contains taboo word. The data are classified from taboo words according to Battistella theory. The meaning by using Abdul Chaer theory. Then, the strategies of translation by using Mona Baker theory. The findings of research shows that there are four types of taboo words, consisting of; 1 data of obscenity, 8 data of epithets, 2 data of vulgarity, 3 data of profanity and also the writer found that epithets data is more dominantly used by nine characters. Furthermore, there are two taboo meanings found, contextual 8 data, connotative 6 and contextual data which is more dominantly used in the movie. Finally, there are three strategies of translation found; translation by more general words 9 data, translation by cultural substitution 3 data, translation by neutral words 2 data and translation by more general words which is more dominantly used in the SpongeBob Movie: Sponge Out of Water.